Different Nitrogen Sources to Improve the Quality of Spirulina platensis Culture in Mass Scale. Issue 1 (1st December 2022) - Ruliaty, L; Amalia, I R; Sari, R I; Aulia, R
Abstract: The research aimed to determine the effect of adding different sources of nitrogen to mass culture of Spirulina platensis . Materials needed for this test was culture media volume 1000 m 3, fertilizer were SP-36 (40 ppm), ZA (10 ppm), EDTA (5 ppm) dan FeCl3 (1 ppm), Vitamin B-12 (0, 001 ppm) and initial density of S. platensis was 10x10 3 sinusoid/ml. The test was carried out in two steps, firstly was the addition of nitrogen source from urea with doses of 80 ppm, 150 ppm and 200 ppm. Secondly, concurrent use of the best urea concentration from first treatment and potassium nitrate addition with doses of 50 ppm, 100 ppm and 150 ppm. Spirulina platensis was cultured on mass scale for 5 days until harvest. The first test showed that the dose of urea 80 ppm gave the highest growth rate (1, 15 sinusoid/day) and the fastest generation time (0, 60 hours) compared to doses of 150 ppm and 200 ppm. Protein content of Spirulina platensis added with 80 ppm of urea was also the highest (58, 04%) compared to 150 ppm and 200 ppm. The results from second test showed concurrent use of urea 80 ppm and potassium nitrate 100 ppm to Spirulina platensis culture gave the highest growth rate (0, 45 sinusoid/day) and the fastest generation time (1, 54 hours) compared to those which added with 150 ppm and 50 ppm of potassium nitrate. Protein content of S. platensis with concurrent addition of urea 80 ppm and potassium nitrate 100 ppm was also the highest at 67, 30%, compared to 150 ppm and 50 ppm.